2017
DOI: 10.3390/ijms18112383
|View full text |Cite
|
Sign up to set email alerts
|

KLF2 in Regulation of NF-κB-Mediated Immune Cell Function and Inflammation

Abstract: KLF2 (Kruppel-like factor 2) is a member of the zinc finger transcription factor family, which critically regulates embryonic lung development, function of endothelial cells and maintenance of quiescence in T-cells and monocytes. It is expressed in naïve T-cells and monocytes, however its level of expression decreases during activation and differentiation. KLF2 also plays critical regulatory role in various inflammatory diseases and their pathogenesis. Nuclear factor-kappaB (NF-κB) is an important inducer of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 75 publications
(159 reference statements)
5
106
0
1
Order By: Relevance
“…Next, we analyzed the expression levels of a regulator of T cell quiescence, KLF2 (28). Results presented in Fig.…”
Section: Targeting Of Cd71 With Mab Vip-1 Induces a Hypoproliferativementioning
confidence: 99%
“…Next, we analyzed the expression levels of a regulator of T cell quiescence, KLF2 (28). Results presented in Fig.…”
Section: Targeting Of Cd71 With Mab Vip-1 Induces a Hypoproliferativementioning
confidence: 99%
“…67 The Rho pathway and myocyte enhancer factor-2 binding site of KLF-2 promoter are implicated for statin-induced KLF-2 expression, and KLF-2 plays as a novel nuclear mediator of statin effects in endothelial cells. 68,69 KLF-2 also inhibits NF-κB transcriptional activity and acts as a regulator of inflammation and fibrosis. 69 Upregulation of KLF-2 expression in hepatic endothelial cells by statin treatment limits fibrogenic HSC activation, reduces hepatic oxidative stress, and attenuates the portal blood flow and hepatic vascular resistance, thereby improving endothelial function and preventing hepatic fibrosis.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Further evaluation using a middle cerebral artery occlusion and reperfusion (MCAO/R) rat model supported the conclusion that Ala could (1) alleviate cerebral ischemia-reperfusion injury; (2) reduce neurological deficits, cerebral infarct volume, and brain edema; and (3) attenuate the apoptosis and necrosis of neurons. In sum, Ala demonstrates anti-neuroinflammatory properties that contribute to the amelioration of CNS damage, and it could be a promising candidate for future applications in CNS injury treatment.be found that two signaling pathways stand out as being strongly associated with the production of proinflammatory factors: Nuclear factor kappa light-chain enhancer of activated B cells (NF-κB) [10] and mitogen-activated protein kinase (MAPK) [11].Because it is responsible for the transcription of several proinflammatory cytokines, chemokines, and adhesion molecules, the NF-κB signaling pathway plays a crucial role in many diseases that involve dysregulation of the inflammatory response [12,13]. The NF-κB signaling pathway consists of a series of intracellular secondary reactions [14,15].…”
mentioning
confidence: 99%
“…Because it is responsible for the transcription of several proinflammatory cytokines, chemokines, and adhesion molecules, the NF-κB signaling pathway plays a crucial role in many diseases that involve dysregulation of the inflammatory response [12,13]. The NF-κB signaling pathway consists of a series of intracellular secondary reactions [14,15].…”
mentioning
confidence: 99%